Efficacy of a biofungicide based on Trichoderma afroharzianum CP 24–6 against cacao frosty pod rot under different doses and application timings - Meza-Maicelo, Wagner; Cortez-Lázaro, Anthony; Reyna-Rivera, Enistein R.; Loja-Torres, Melissa I.; Oliva-Cruz, Manuel; Leiva-Espinoza, Santos T. (Frontiers in Plant Science, 2026)
During their development, cacao fruits are the primary target of frosty pod rot (Moniliophthora roreri), a disease that has affected cacao producers in Amazonas, Peru, for more than three decades. The objective of this study was to evaluate the biocontrol potential of two doses of Trichoderma afroharzianum CP 24–6 against artificial infection by M. roreri in cacao fruits at different developmental stages. For this purpose, a biofungicide was formulated using this native species, an endophyte from cacao agroecosystems in the region. After quality control, the biofungicide was applied at two doses (1 × 105 and 1 × 106 conidia/mL) and at three fruit developmental stages (20, 40, and 60 days), generating six treatments through the interaction of both factors. Incidence, external severity, and internal severity were evaluated under a completely randomized block design with a factorial arrangement. The results showed that the interaction between biofungicide dose and fruit age at the time of infection was a key determinant of the biocontrol efficacy exerted by T. afroharzianum. The dose of 1 × 106 conidia/mL exhibited greater effectiveness, particularly in fruits infected at 60 days of development, whereas the 1 × 105 conidia/mL dose was less effective at earlier stages. Application of the biofungicide delayed symptom expression and reduced both external severity and internal severity compared with untreated fruits, which showed higher susceptibility and more severe damage. These findings demonstrate the potential of T. afroharzianum CP 24–6 as a native biofungicide for the sustainable management of cacao frosty pod rot.